2015
DOI: 10.1111/febs.13502
|View full text |Cite
|
Sign up to set email alerts
|

miR‐124 exerts tumor suppressive functions on the cell proliferation, motility and angiogenesis of bladder cancer by fine‐tuning UHRF1

Abstract: UHRF1, an epigenetic factor, is implicated in various cellular processes of tumorigenesis. However, the modulation of UHRF1 expression in human bladder cancer at post‐transcriptional levels remains unclear. Here, we report that miR‐124 suppresses expression of UHRF1 to affect the progression of human bladder cancer through competitive binding of the same region of its 3′‐UTR. We show that compared with corresponding normal tissues, UHRF1 is upregulated and miR‐124 is downregulated in bladder cancer tissues, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…Moreover, miR-124 expression was down-regulated in bladder cancer tissues compared with corresponding adjacent non-tumor tissues which were consistent with previous report [53]. In bladder cancer tissues, miR-124 expression was inversely correlated with XIST and AR expression, respectively.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, miR-124 expression was down-regulated in bladder cancer tissues compared with corresponding adjacent non-tumor tissues which were consistent with previous report [53]. In bladder cancer tissues, miR-124 expression was inversely correlated with XIST and AR expression, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…According to previous studies, miR-124 plays a suppressive role in cancers [20]. The role of miR-124 in bladder cancer was reported [21]. Here, we hypothesized that XIST might act as a ceRNA to sponge miR-124, thus to regulate AR expression.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Wang et al (25) found that human bladder transitional cancer cell lines J82 and T24 generated VM formation, and this was inhibited by downregulation of UHRF1 via miR-124. Likewise, in the current study, we confirmed that bladder transitional cancer cell lines UM-UC-3 and J82 can generate VM structures in a 3-D Matrigel culture, but the immortalized human bladder epithelium cell line SV-HUC-1 did not exhibit this ability, even when the seeding concentration was higher or the observation time was longer.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-124 is predominantly expressed in normal brain and plays an important role in neural processes from normal neural cell function to the development of central nervous system tumors [24]. Several studies have suggested that miR-124 is significantly downregulated in several human cancers, such as bladder, breast and lung cancer [25][26][27]. Recently, a number of experiments have shown that miR-124 is involved in the regulation of cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%